Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Cristian Pattaro (Nature Portfolio, 2016)
Reduced glomerular filtration rate (eGFR) is a hallmark of chronic kidney disease. Here, Pattaro et al. conduct a meta-analysis to discover several new loci associated with variation in eGFR and find that genes associated with eGFR loci often encode proteins potentially related to kidney development.